1996
DOI: 10.1093/hmg/5.8.1117
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for an imprinted gene for neonatal diabetes localised to chromosome 6q22-q23

Abstract: Transient neonatal diabetes mellitus (TNDM) is a rare form of childhood diabetes which usually resolves in the first 6 months of life but which predisposes to type 2 diabetes of adult onset. We recently reported paternal uniparental isodisomy of chromosome 6 (UPD6) in two children with TNDM and proposed that there may be an imprinted gene important in the aetiology of diabetes on chromosome 6. We now describe two unrelated families which independently suggest that the gene is imprinted, is paternally expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
79
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(84 citation statements)
references
References 19 publications
4
79
0
1
Order By: Relevance
“…In group 2, 11 patients were identified with a duplication of part of chromosome 6q. These included all 7 familial cases (families K and L) and 4 sporadic cases ( (16,17), and 9 were identified using quantitative PCR of ESTs and STSs from the region (Fig. 1, ID [12][13][14][15][16][17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In group 2, 11 patients were identified with a duplication of part of chromosome 6q. These included all 7 familial cases (families K and L) and 4 sporadic cases ( (16,17), and 9 were identified using quantitative PCR of ESTs and STSs from the region (Fig. 1, ID [12][13][14][15][16][17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…The association is now firmly established, although 2 cases of paternal UPD6 have been reported in older patients with no early history of TND, which cannot yet be explained (14,15). We and others have subsequently shown that several nondisomic children with TND have paternally inherited duplications within the long arm of chromosome 6 (6q23-24) (12,(16)(17)(18). Evidence from one of these families suggested that inheritance of an identical duplication from the mother did not lead to TND (16).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…These findings suggested the presence of an imprinted gene on chromosome 6. Later studies provided further evidence of the involvement of an imprinted gene in this disease and proposed that a candidate gene for TNDM lies within the chromosomal region 6q24.1-q24.3 between markers D6S1699 and D6S1010 (Temple et al, 1996;Gardner et al, 1999). Analysis of the CpG islands in the TNDM critical region for the presence of methylation differences between maternal and paternal alleles, using DNA from TNDM patients with paternal UPD 6 and normal controls, suggested LOT1/ZAC1 as a candidate imprinted gene for this disease (Gardner et al, 2000).…”
Section: Imprinting and Chromosomal Duplicationmentioning
confidence: 99%